Rapid and in situ optical detection of trace lithium in tissues - Ahmed, Irfan (Biomed Opt Express, 2018)
Lithium-based medications are used successfully to treat many mental disorders, including bipolar disorder and Alzheimer’s disease. However, the therapeutic mechanisms are not well characterized due to limitations in detecting lithium in organs and cells. This limits the ability to improve lithium-based treatments. To address this need, laser-induced breakdown spectroscopy (LIBS) is developed for the rapid and in situ detection of lithium in biological tissues. Pronounced lithium emissions are observed at 670.7nm from the rat thyroid, salivary, and mammary glands when lithium is administered orally. Calcium, carbon, magnesium, sodium, potassium, and iodine emissions are also observed. The lithium emission intensity is positively correlated with tissue lithium concentration, which is ~1ppm. The limit of detection for lithium is determined to be ~0.1ppm. Thyroid lithium intensity increases while iodine intensity decreases. The reduced intrathyroidal iodine following treatment likely impairs hormone production. Further, the presence of lithium in the salivary and mammary glands makes these glands the likely conduits for lithium to enter the saliva and breast milk, respectively. LIBS is well suited for characterizing the distribution of lithium, and other elements, across the body. This optical method can potentially be adapted for use in vivo and in humans.